Qâmûs al-Af’âl al-Muta’addiyah bi al-H?af al-Jarr al-Takhrîj min al-Qur’ân al-Karîm - Bashirotul Hidayah (INSTITUT AGAMA ISLAM BANI FATTAH (IAIBAFA), 2014)
In grammatical Arabic, there is a verb that has a relationship (ta’allûq) with the letter jar. One letter can have two or more relationships that have variants different meanings. The absence of further explanation in the classical books makes it difficult ta’allûq understand it, so that the codification into a decent existence.